2021
DOI: 10.2144/fsoa-2021-0012
|View full text |Cite
|
Sign up to set email alerts
|

The COVID-19 Pandemic: a Threat to Antimicrobial Resistance Containment

Abstract: As of 23 April 2021, the outbreak of COVID-19 claimed around 150 million confirmed cases with over 3 million deaths worldwide. Yet, an even more serious but silent pandemic, that of antimicrobial resistance (AMR), is likely complicating the outcome of COVID-19 patients. This study discusses the current knowledge on the emergence of the SARS-CoV-2 and highlights the likely contribution of the COVID-19 pandemic on the escalation of AMR. COVID-19 engenders extensive antibiotic overuse and misuse, and will undoubt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 36 publications
(54 reference statements)
0
43
0
2
Order By: Relevance
“…This can potentially be attributed to a number of factors including social distancing measures and reduction in medical activities [67][68][69] . Nonetheless, inappropriate use of antibiotics during COVID-19 is a potential driver of the silent AMR pandemic [24,70] . However, with current changes observed in global human behaviour, relating to personal hygiene, and increased interest in infection control since the emergence of this pandemic, we should see a rise in AMS activities globally [71] .…”
Section: -Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This can potentially be attributed to a number of factors including social distancing measures and reduction in medical activities [67][68][69] . Nonetheless, inappropriate use of antibiotics during COVID-19 is a potential driver of the silent AMR pandemic [24,70] . However, with current changes observed in global human behaviour, relating to personal hygiene, and increased interest in infection control since the emergence of this pandemic, we should see a rise in AMS activities globally [71] .…”
Section: -Discussionmentioning
confidence: 99%
“…Consequently, this review aims at building on these publications through identifying the prevalence of bacterial co-infection, and the prevalence of antibiotic use in patients with COVID-19 across multiple countries and regions to guide future prescribing. This includes reducing the inappropriate use of antimicrobials during the COVID-19 pandemic where inappropriate use is a potential driver of antimicrobial resistance (AMR) [24, 25, 34]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, 74.6 % of patients are given antibiotics as a preventative measure to avoid secondary infection ( Langford et al, 2021 ). This scenario suggests that antibiotics are being used inappropriately and possibly excessively in COVID treatment, which may result in a significant increase in antibiotic-resistant organisms in a short period of time ( Founou et al, 2021 ; Livermore, 2021 ). Antibiotic resistance is already predicted to become a pandemic by 2050, causing 10 million deaths per year worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the results of a large placebo-controlled trial of vaccines from Pfizer and Moderna have shown that two repeated doses of the vaccine are highly effective in preventing COVID-19 (more than 90%) [10,11]. Based on the results of these clinical trials, vaccination with multiple types of COVID-19 vaccines developed by several pharmaceutical companies began worldwide at the end of 2020 or in early 2021 [12]. While hopes for pandemic containment through vaccination are increasing, the emergence of SARS-CoV-2 variants with amino acid mutations in the antigenic determinants of spike proteins, as described above, has been reported worldwide.…”
Section: Introductionmentioning
confidence: 99%